Rancang Bangun Monitoring Daya, Suhu, dan Getaran Terhadap Kecepatan Motor 1 Fasa Berbasis Internet of Things - Abdul Kodir Albahar; Nur Muhamad Veriantama (Teknik Elektro Universtias Krisnadwipayana, 2026)
The performance of induction motors in modern industries is crucial to prevent downtime due to unrecorded motor damage during preventive maintenance. The utilization of the Internet of Things (IoT) is highly beneficial due to the ubiquitous use of the internet, which can be leveraged to develop and implement a motor monitoring tool. This research employs various sensors, such as the PZEM004T-Open CT sensor for power detection, the SW-42 sensor for vibration detection, an infrared sensor for motor speed detection, and the DHT11 sensor for temperature detection, as well as an amp clamp meter, multitester, and thacometer. These tools are useful for detecting motor performance over time. This is a quantitative study. The results yield data in the form of numerical measurements that can be analyzed and compared with existing standards. The average calculated voltage value is 1.5 volts with an average deviation of 1.47%. The average current value is 0.01 amperes with an average deviation of 6.06%. The average power value is 0.52 watts with an average deviation of 1.67%. The average rotational speed is 221.5 RPM with an average deviation of 12.92%. The average vibration value is 1.53 mm/s, with a noticeable increase in vibration to be cautious of when the dimmer is set at 60%, which shows a vibration value of 0.36 mm/s. The average motor temperature is 37.9 ℃